Studi Kecepatan Tanah Maksimum (PGV), Percepatan Tanah Maksimum (PGA) dan Skala Intensitas Kerusakan (MMI) Gempa Bumi di Kabupaten Bengkulu Utara - Arrahma, Mawadatul; Hadi, Arif Ismul; Harlianto, Budi (Navigation Physics : Journal of Physics Education, 2024)
North Bengkulu has a significant level of earthquake virility. One method to identify this virginity is through research into the correlation between Peak Ground Acceleration (PGA), Peak Ground Velocity (PGV), and Modified Mercalli Intensity (MMI). The data used came from the United States Geological Survey (USGS), which is secondary data. The data processing process involves applying an empirical formula that describes the relationship between PGV and intensity, as well as PGA and earthquake intensity. Furthermore, the results of the PGA & PGV calculations are incorporated into ArcGis 10.8 to create PGA&PGV contour maps, and the relationship curves of PGA to PGV, PGA, and MMI, and PGV & MMI using Excel 2019. The results of the analysis show that the largest PGV PGA value is in Arga Makmur district which has a intensity of 4.